Decision Support System for Receiving Waste Retribution at the Housing and Sanitation Services Uses the Naïve Bayes Algorithm - Rachmat Rachmat; Abdul Ibrahim (Indonesian Scientific Journal, 2021)
The Department of Settlements and Cleanliness of Pangkep Regency is tasked with maintaining the cleanliness and comfort of Pangkep Regency so that Pangkep City becomes a clean and beautiful city. Duties and responsibilities are on the Department of Settlements and Sanitation to jointly maintain the city of Pangkep so that it remains clean and beautiful. The waste generated by the community can generate retribution for Pangkep Regency which will later be managed into the Pangkep Regency APBD every year, so far the Settlement Service is and the cleanliness of Pangkep Regency in taking waste retribution is still used in traditional ways by using a semicomputer or manual system. So that the receipt of waste retribution is prone to being diverted by irresponsible people, therefore the writer tries to create a system which later can control waste retribution. admin. With a computerized system using a visual basic application program and using the Naïve Bayes algorithm with an accuracy of 77, 50% where later employees in charge of transporting waste from households, restaurants, hospitals and markets are in accordance with the costs set by the community and government, in this case the Department Settlement and Cleanliness of Pangkep Regency. The employee in charge will distribute tickets to every household, restaurant, hospital and market every day so that how many tickets are carried by the employee will be calculated the remaining tickets multiplied by the ticket price based on the color of the tickets that have been determined by the Pangkep District Office of Settlement and Sanitation.